Silent predators: Revealing the parasites of Himalayan musk deer (Moschus leucogaster) in Manaslu Conservation Area, Nepal - Bishnu Achhami; Shila Gurung; Sujan Deshar; Sapana Khaiju; Lekha Kumari Thapa; Sabita Gurung (International Journal for Parasitology: Parasites and Wildlife, 2025)
Parasites pose a significant threat to wildlife, yet their impact remains largely understudied, with limited research conducted on the parasites of wild animals. This study provides the first quantitative analysis of gastrointestinal parasites in the endangered Himalayan musk deer (Moschus leucogaster), while also documenting a wider variety of parasites within the Manaslu Conservation Area (MCA), Nepal. Non-invasive sampling of 52 fresh fecal pellets from Kaltal (n = 28) and Mugumba (n = 24) revealed a high prevalence (94.2 %) of gastrointestinal parasites including two nematodes (Pneumocaulus sp. and Strongyle) and one parasitic protist (Eimeria sp.). Pneumocaulus sp. was the most abundant parasite, present in 100 % of Kaltal and 87.5 % of Mugumba samples. Strongyle was absent in Kaltal but had a lower prevalence (12.5 %) in Mugumba. Co-infection was identified in 25 % of samples, which could potentially threaten the health of musk deer. Statistical analysis with Firth's logistic regression indicated that higher elevations were associated with a lower chance of strongyle being present (p = 0.0057). Slope, aspect, and distance from water or roads did not significantly affect the distribution of the parasites. Parasite communities showed moderate similarity between the sites (Bray-Curtis dissimilarity = 0.22; Jaccard similarity = 0.67), with no significant difference in prevalence between Mugumba and Kaltal. Pneumocaulus sp. was found widely over the elevation gradient, most typically at 3600–3700 m, while strongyle was confined to lower elevations below 3500 m. This baseline study demonstrates the substantial gastrointestinal parasite burden in Himalayan musk deer and underscores the need for conservation and health management efforts for this endangered species in the MCA. Holistic conservation methods, including habitat management, disease detection, and further studies, including a large-scale sampling, seasonal data collection, and molecular techniques, can significantly enhance our understanding of the intricate relationship among parasites, hosts, and their environment in the endangered species conservation.